2023
DOI: 10.1159/000533134
|View full text |Cite
|
Sign up to set email alerts
|

Personal Narratives of 10-Year-Old Children in Iceland: Verbal Productivity, Word Diversity, and Topics

Jóhanna T. Einarsdóttir,
Erna Þráinsdóttir

Abstract: Introduction: The feasibility of using a standard protocol, labelled as the Global TALES, to elicit personal stories was tested across 10 different countries between 2019 and 2021. Personal narratives have not been investigated in Iceland in a similar way. The aim was to explore personal narratives of monolingual children in Iceland by using the Global TALES (2018) protocol to investigate verbal productivity, word diversity, and narrative topics. Methods: Twenty-seven children (ages 9;8 – 10;9) with typical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The first three articles of this special issue report on the feasibility of using the Global TALES protocol with children from Iceland [5], Turkey [6], and Ireland [7]. Despite large individual variability in language productivity and semantic diversity within each language group, all three studies found that all six prompts were successful in eliciting personal narratives from most of the children.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first three articles of this special issue report on the feasibility of using the Global TALES protocol with children from Iceland [5], Turkey [6], and Ireland [7]. Despite large individual variability in language productivity and semantic diversity within each language group, all three studies found that all six prompts were successful in eliciting personal narratives from most of the children.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
“…Despite large individual variability in language productivity and semantic diversity within each language group, all three studies found that all six prompts were successful in eliciting personal narratives from most of the children. Einarsdóttir and Þráinsdóttir [5] reported on 27 ten-year-old Icelandic-speaking children and found that only two children could not provide an answer to one of the six prompts. Maviş and Yaşar-Gündüz [6] assessed ten 7-year-old and ten 10-year-old Turkish-speaking children and reported that all children produced a response to all of the prompts.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation